Social Security and Ways to Enhance It in Libyan Society: An Analytical Sociological Study in Light of Contemporary Social Theories (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the state of social security in Libyan society in light of the political, social, and economic transformations that have taken place since 2011, with a focus on the factors contributing to the decline of social cohesion and the rise of societal insecurity. The study is based on the assumption that the crisis of social security in Libya is linked to the interaction of several factors, most notably the fragility of state institutions, political division, weak distributive justice, and the erosion of social capital.The study adopts a descriptive-analytical approach, drawing on a theoretical framework that integrates human security theory, social cohesion theory, and social capital theory, along with the concepts of distributive justice and relative deprivation. It also relies on a review of recent studies addressing social security, political development, and civil society in Libya.The findings indicate that ongoing institutional division, the spread of armed groups, the weakness of social control institutions, as well as increasing corruption and economic inequality, have contributed to growing social disintegration and alienation within Libyan society. The results also reveal a decline in social trust and the rise of tribal and regional loyalties at the expense of national identity, negatively affecting societal stability.The study recommends adopting a comprehensive approach to rebuilding social security by strengthening distributive justice, supporting state institutions and civil society, launching national reconciliation initiatives, and reforming the educational and media systems to promote citizenship, tolerance, and social cohesion.